Planting steel reinforcement for concrete columns - Kharnoob Majid (Magazine of Civil Engineering, 2023)
This study presents a scenario where the embedding of dowel reinforcement for new columns was inadvertently omitted during the casting of concrete columns. This oversight necessitated the implantation of steel reinforcement into pre-existing cast areas. Owing to the high density of the primary slab reinforcement, implantation was feasible only up to half the slab's thickness. By modifying the superplasticizer (SP) dosage during mixing, we achieved a consistent slump of approximately 150 mm across various concrete mixes, ensuring that both slump and slump flow remained within expected limits. The properties of these mixes, both in their fresh and hardened states, are detailed in Table 2. The sieve segregation index consistently remained below 1.3 %, indicating exceptional cohesion in all concrete mixes. In fact, no segregation was observed, with all measured segregation widths being zero. In terms of strength, the cylinder strength increased significantly with the increase in fiber volume from 0 % to 2 %. This study also examines the impact of steel reinforcement, utilizing 8 mm diameter steel bars over a 30 cm length, planted at two different angles (90 and 45 degrees). The concrete column samples were subjected to uniaxial compressive load post-implantation. Results indicate that the implantation process generally led to an increase in the initial compressive strength of the concrete samples. Specifically, specimens with 30 cm reinforcement planted at distances of 55 mm and 35 mm exhibited an average strength increase of 23 % and 17 %, respectively.